Survival in soil and detection of co-transformed Trichoderma harzianum by nested PCR - Queiroz, Paulo Roberto; Valadares-Inglis, Maria Cléria; Inglis, Peter Ward (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to evaluate the survival of two Trichoderma harzianum cotransformants, TE 10 and TE 41, carrying genes for green fluorescent protein (egfp) and for resistance to benomyl, during four weeks in a contained soil microcosm. Selective culture media were used to detect viable fungal material, whose identity was confirmed by the observation of the fluorescent phenotype by direct epifluorence microscopy. PCR using two nested primer pairs specific to the egfp gene was also used to detect the transformed fungi. Although it was not possible to reliably detect the egfp gene directly from soil extracts, an enrichment step involving selective culture of soil samples in liquid medium prior to DNA extraction enabled the consistent detection of the T. harzianum co-transformants by nested PCR for the duration of the incubation period.